Pengaruh Pendidikan Kesehatan Terhadap Perilaku Melakukan Sadari Pada Wanita Usia Subur: Literature Review - Solehati, Tetti; Mahmuudah, Lu'lu N; Pratiwi, Rery Yuliani; Fikri, Auliya Ramanda; Putri, Sarah Rauzana; Elhaqqa, Arina; Miliarta, Evita R; Ardliana, Ratna R; Eldiana, Liesta; Indriana, Vivi V; Supriadi, Supriadi (Jurnal Keperawatan Muhammadiyah, 2019)
Introduction: Breast cancer is a malignant disease in women where the mortality rate of sufferers increases every year. The importance of early detection steps to help women overcome these problems, one of them by doing breast self-examination (Breast Self-Examination) Behavior of a person to do breast self-examination is basically different, this is influenced by several factors, one of which is knowledge. Objective: This literature review aims to determine the effect of health education on the behavior of women of childbearing age in conducting BSE actions. Methods: Search for articles using an electronic database that is google schoolar, Science Direct, and Pubmed. Keywords used in Indonesian and English are "women", "BSE health education", "Women", and "Health Promotion Breast Self-Examination". The article search results were found on the Google Scholar website of 3,090, Science Direct 4,875 results, and PubMed 224 results. The articles were then sorted according to topic so that 8 research articles were collected which were considered to be representative of all research articles on women and BSE health education. Results: It was found that BSE health education can reduce the risk of breast cancer and improve the quality of health promotion in women. Conclusions and Recommendations: this study provides valid evidence that health education influences the behavior of women to make breast self-examination. Further studies related to health education can be done in more depth about which actions are most effective in increasing behavior in doing breast self-examination.